Emotion Regulation Strategies Can Predict Task-Switching Abilities in Euthymic Bipolar Patients - Gul, Amara; Khan, Kamran (Frontiers in Human Neuroscience, 2014)
This study examined task switching abilities and emotion regulation strategies in euthymic bipolar patients (EBP). 40 EBP and 40 healthy individuals performed face categorization tasks where they switched between emotion and non-emotion (i.e., gender) features among faces and completed emotion regulation questionnaire (Gross & John, 2003). Subject groups showed substantial differences in task switching abilities and emotion regulation strategies: (1) There was a dissociation between emotion and gender classification in euthymic bipolar patients. The switch cost was larger (i.e., higher reaction times on switch as compared to no-switch trials) for gender categorization as compared to the emotion categorization task. In contrast, such asymmetries were absent among healthy participants. The differential pattern of task switching reflected functional disturbances in frontotemporal neural system and an attentional bias to emotion features of the faces in EBP. This suggests that when a euthymic bipolar patient is preoccupied with emotion recognition, an instruction to perform gender categorization results in greater cost on reaction times. (2) In contrast to healthy individuals, EBP reported more frequent use of emotion suppression and lesser use of cognitive reappraisal as emotion regulation strategy. (3) Emotion regulation was found to be a significant predictor of task switching abilities. It is argued that task switching deficits rely on maladaptive emotion regulation strategies in EBP specifically when tasks of emotional significance are involved.